2019
DOI: 10.1155/2019/6403504
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Trioxide in Synergy with Vitamin D Rescues the Defective VDR-PPAR-γFunctional Module of Autophagy in Rheumatoid Arthritis

Abstract: Dysregulated autophagy leads to autoimmune diseases including rheumatoid arthritis (RA). Arsenic trioxide (ATO) is a single agent used for the treatment of acute promyelocytic leukemia and is highly promising for other malignancies but is also attractive for RA, although its relationship with autophagy remains to be further clarified and its application optimized. For the first time, we report a defective functional module of autophagy comprising the Vitamin D receptor (VDR), PPAR-γ, microtubule-associated pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…Proliferation of OA-derived FLS was evaluated using the Cell Counting Kit-8 (CCK-8, Dojindo Molecular Technologies, Kumamoto, Japan), as described previously [29]. Brie y, 10 4 cells were seeded in a 96-well plate.…”
Section: In Vitro Proliferation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Proliferation of OA-derived FLS was evaluated using the Cell Counting Kit-8 (CCK-8, Dojindo Molecular Technologies, Kumamoto, Japan), as described previously [29]. Brie y, 10 4 cells were seeded in a 96-well plate.…”
Section: In Vitro Proliferation Assaymentioning
confidence: 99%
“…On day 42 from the initial collagenase VII injection, mice were sacri ced. The distal femur and proximal tibia were cut with a blunt scissor to obtain knee joint tissues and scanned with a Quantum GX microcomputed tomography (micro-CT) imaging system (Perkin Elmer, Waltham, MA, USA) [29] to investigate the effect of SDF-1 on the three-dimensional (3D) bone structure in collagen-induced OA mice.…”
Section: Microcomputed Tomography (Micro-ct) Imagingmentioning
confidence: 99%
“…Many requests came to our lab as a result, including one from Nobel Laureate Dr. Mario Capecchi1(Figure 6). Mi-2 [19][20],HSF1/Hsp90 [20], mTOR and Vitamin D receptor [4,15] alongside their focused endogenous regulatory network to protect human from "catastrophes" as "Dam"controls the flood. As an instructor in Harvard medical school, particularly I and others found that mTOR and its directs autophagy to play a vital role in longevity and aging-related complex diseases,e.g.OA, cancer, neurodegenerative diseases,cardiovascular diseases(CVD).…”
Section: My Personal Journeymentioning
confidence: 99%
“…The data showed that there is no significant change in cell viability (Fig. 1C) [2]. As 2 O 3 at the lowest effective concentration of 0.5 μM selectively inhibited the differentiation of CD4 + T cells into IL-17 + CD4 + T cells (Fig.…”
Section: Datamentioning
confidence: 99%